ScFv antibody: Principles and clinical application - Abd Manaf, Ali (2012)
V View ft N... (167) To date generation of single-chain fragment vanable (scFv) has become an established technique used to produce a completely functional antigen-binding fragment in bacterial systems The advances in antibody engineering have now facilitated a mole efficient and generally applicable method to produce Fv fragments. Basically scFv antibodies produced from phage display can be genetically fused to the marker proteins. such as fluorescent proteins or alkaline phosphalase These bifunctional proteins haring both antigen-binding capacity and marker achaty can be obtained from transformed bacteria and used for one-step immunodetection of biological agents Alternatively. antibody fragments could also be applied in the construction of immunotcouns therapeutic gene delwery and anticancer intrabodies for therapeutic purposes This paper 6110AdOS an ovemew of the current studies on the principle generation and application of scFv The potential of scFv in breast cancel research is also discussed in this paper Copynght 2012 Zuhaida Asra Mmad et at